ANALYSIS OF THE USE OF E-LEARNING ON LEARNING MOTIVATION IN STUDENTS - Ridwan Agustian Nur; Adi Rosadi; Dede Ridwan; Irsan Apriandinata (Jurnal Scientia, 2022)
The phenomenon that exists in the field is that students still low interest in learning. One of the solutions used is by implementing e-learning. This study uses a qualitative approach with a descriptive verification method with a research sample of 120. Data collection using a questionnaire Data analysis techniques were carried out using the Structural Equation Model (SEM) using the Lisrel 8.8 software. Data quality test consisting of validity and reliability tests; then conducted a feasibility test of the model based on the Goodness of Fit (GoF) value; then tested the hypothesis with SEM technique using AMOS lisrel 8.8 software. There is a significant effect between the use of e-Learning on learning motivation of 77.44%, while the remaining 22.6% comes from influences outside the research variables.